The Electromagnetic Meters of Non-homogeneous Flow - Šimeliūnas, R.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2005)
The electromagnetic flow meter with rectangular duct and linear electrodes is convenient for measurement of non-homogeneous flow. If uniform magnetic field is created in all volume of duct of meter and the magnetic admixtures are absent, the non-homogeneous flow can be measured without the complementary error. When the magnetic field is non-uniform in some volume of duct, the error of measurement appears. The maximal error can be calculated, if the relative part of the electrode signal, which is created in the part of duct with non-uniform magnetic field, is evaluated. The distribution of the density of virtual current and magnetic flow can be evaluated using the analogy with the field of line of two wires. The error can be diminished, if the part of uniform magnetic field is increased or the volume concentration of admixtures is diminished. Ill. 3, bibl. 4 (in Lithuanian; summaries in Lithuanian, English and Russian).